Exploring mathematics teachers' experiences with professional development programs: A Critical autoethnographic study - Almalki, Yahya Hamed Ahmad; Alsulami, Naif Mastoor (Journal of Educational and Psychological Sciences, 2022)
This paper aims to critically examine the experiences of my fellow mathematics teachers about professional development programs, to explore and deeply understand their experiences with professional development programs, to know their attitudes and the level of their participation and interaction with her, in addition to obstacles encounter as teachers in professional development programs. In this research, I followed the auto-critical ethnographic approach, which allowed me to critically reflect on my previous experiences with professional development programs, I also conducted interviews with six of my fellow mathematics teachers. In this research, I found that one of the most ssignificant obstacles that may have contributed to the reluctance of mathematics teachers from professional development programs is the presence of negative perceptions of mathematics teachers toward development programs that significantly affect the extent of their interest in those programs; I believe that these negative perceptions and attitudes were formed in the minds of mathematics teachers as a result of their low awareness of professional development programs, inefficient raining environment in which the basic elements for conducting training courses are not available in the hoped manner, also, the training methods provided are dominated by the traditional lecture method. Accordingly, this paper recommends the necessity of educational activities in which teachers engage critically on their attitudes and perceptions, in addition to the need of encouraging mathematics teachers towards professional development programs by the school administration and educational supervision, as their role is important to stimulate teacher motivation, in addition to contributing to overcoming the difficulties facing the teacher to enrol in these programmes.
Keywords: professional development programs; teachers' experiences with training programs; ethnographic research